Knowledge sharing networks and performance - Marques, Dulce Vieira (2008)
The present investigation aims to analyse the relationship between knowledge sharing behaviours and performance. The former behaviours were studied using Social Network Analysis, in an attempt to characterise knowledge sharing networks. Through identification of central individuals in these networks, we made analysis of the association between this centrality and individual performance. A questionnaire was developed and applied to a sample of workers in a Portuguese organisation (N=244). The final conclusions point to a positive association between these behaviours and individual performance.